2014
DOI: 10.1007/978-1-4614-3209-8_43
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Ex Vivo Characterization of the Immunophenotype and Function of Microglia/Macrophage Populations in Normal Dog Retina

Abstract: Microglia are the primary resident immune cells of the retina and are involved in the pathogenesis of various retinal diseases. In this study, we optimized experimental conditions to isolate microglia from canine retinas and characterized ex vivo their immunophenotype and function using flow cytometry (FACS). The most suitable protocol included a mechanical dissociation of the retina and an enzymatic digestion using DNAse and collagenase. Extraction was carried out by density gradient centrifugation, and retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Percoll gradient for the isolation of microglia is performed in less time-consuming manner and requires less expensive equipment, which is suitable for further flow cytometry analysis, RNA isolation for gene expression by real-time PCR or microarrays, and for functional assays including cytokine production, chemotaxis, and phagocytosis [ 2 ]. In this study, Percoll gradient was used to isolate retinal microglia, in similar way as the method presented by Genini et al [ 26 ]. We uniquely apply this method to the isolation of retinal microglia in COH rats.…”
Section: Discussionmentioning
confidence: 99%
“…Percoll gradient for the isolation of microglia is performed in less time-consuming manner and requires less expensive equipment, which is suitable for further flow cytometry analysis, RNA isolation for gene expression by real-time PCR or microarrays, and for functional assays including cytokine production, chemotaxis, and phagocytosis [ 2 ]. In this study, Percoll gradient was used to isolate retinal microglia, in similar way as the method presented by Genini et al [ 26 ]. We uniquely apply this method to the isolation of retinal microglia in COH rats.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have reported the CD44 expression in microglia; canine retinal microglia in normal condition [21], microglia after ischemic brain injury of the rat [10,11], and microglia in Parkinson mice model by treatment with α-synuclein [14]. However, some studies have showed CD44 expression in astrocytes during development and adult; astrocyte precursor cells in developing chick [4,5], mice and rat [6,7,22], Müller glial cells in mice retina [9].…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes can secrete vasoactive substances that regulate retinal vascular tone [23]. Retinal microglia present as a resident population of immunocompetent cells [24]. The retina blood supply comes from the central retinal artery feeding the inner retinal layers and choriocapillaries for the outer layers: photoreceptor layer, ONL, and OPL [25].…”
Section: Retinal Organizationmentioning
confidence: 99%